High naevus count and MC1R red hair alleles contribute synergistically to increased melanoma risk. (1st November 2019) - Duffy, D.L.; Lee, K.J.; Jagirdar, K.; Pflugfelder, A.; Stark, M.S.; McMeniman, E.K.; Soyer, H.P.; Sturm, R.A.
Summary: Background: A high total body naevus count is the highest risk factor for melanoma; the phenotype of red hair colour, freckling and pale skin that burns easily, produced by MC1R R alleles, also predisposes to melanoma. Objectives: To determine whether the known melanoma risk factors of high naevus count and red hair or MC1R R alleles act synergistically to increase melanoma risk. Methods: The Brisbane Naevus Morphology Study involved 1267 participants from volunteers presenting at a melanoma unit, dermatology outpatient clinic, private dermatology clinics, the Brisbane Longitudinal Twin Study and the QSkin Study. We examined pigmentation characteristics, total body naevus ≥ 5 mm count, and MC1R, ASIP and CDKN2A genotype in participants with and without a personal history of melanoma, living in Queensland, Australia, which is an area of high ultraviolet radiation. Results: Cases were older than controls (median 57 vs. 33 years). Compared with individuals with dark brown hair and zero to four naevi, individuals with red hair and ≥ 20 naevi had a melanoma odds ratio of 10·0 (95% confidence interval 4·2–24·3). Individuals with MC1R R / R genotype and ≥ 20 naevi (≥ 5 mm diameter) had a melanoma odds ratio of 25·1 (95% confidence interval 8·4–82·7) compared with wild‐type (WT)/WT individuals with zero to four naevi. The highest risk group is Australian men with the MC1R R / R genotype and ≥ 20 moles, who have an absolute risk of melanoma to age 75 years of 23·3%, compared with 0·8% for men with the WT / WT genotype and zero to four naevi. Conclusions: Patients who live in areas of high ultraviolet radiation, and have many large naevi and the red hair colour phenotype, particularly those with the MC1R R / R genotype, have a high risk of melanoma above the threshold recommended for screening in other cancers. Therefore, they should undergo intensive physician‐led surveillance. What's already known about this topic? A high number of acquired melanocytic naevi, the red hair phenotype and MC1R R alleles all independently increase melanoma risk. Women with atypical naevi have an increasing melanoma risk gradient from darker hair to lighter hair. Women with many naevi have an increasing melanoma risk gradient from those with no elements of the red hair phenotype, to those with freckles but not red hair, to those with red hair. What does this study add? In Queensland, Australia, people with ≥ 20 naevi (≥ 5 mm diameter) and MC1R R / R genotype have a 25‐fold increased melanoma risk, relative to people with zero to four naevi and the MC1R WT / WT genotype. In Queensland, individuals with ≥ 20 naevi and the MC1R R / R genotype have an absolute melanoma risk to age 75 years of 23·3% for men and 19·3% for women. This effect is independent of CDKN2A genotype. Further research is required to determine the effect of areas of lower ultraviolet radiation, as this study took place in the Queensland, Australia, which is an area of high ultraviolet radiation. MC1R R / r genotype is associated with increased total body naevus count but this is not the case for R / R . What is the translational message? Patients with many large naevi and the red hair colour phenotype, particularly those with an MC1R R / R genotype, have an unusually high risk of melanoma. In a high ultraviolet environment, this risk exceeds the threshold recommended for screening in other cancers, and such individuals should undergo intensive, regular, physician‐led surveillance. Patients with many large naevi but with non‐red colour hair may benefit further from clinical MC1R genotyping.